HIV-1 drug resistance and genetic clustering among ART-treated individuals with virologic failure in Aksu, China - Dai, Zhenzhen; Li, Hu; Xu, Mingyu; Feng, JiangTao; Sun, Liwen; Lu, Di; Bi, Yuxue (Frontiers in Microbiology, 2026)
BackgroundAksu Prefecture is among the regions most heavily affected by HIV-1 in China, yet data on acquired drug resistance (ADR) among antiretroviral therapy (ART)–treated individuals with virologic failure remain limited. This study aimed to characterize the prevalence, mutation patterns, and genetic clustering of drug resistance mutations (DRMs) in Aksu.MethodsWe conducted a retrospective study among ART-treated individuals with virologic failure in Aksu Prefecture from 2022 to 2023. HIV-1 pol sequences were obtained from 675 individuals to identify DRMs. Genetic networks were constructed to assess clustering among individuals harboring DRMs (n = 407). Univariable and multivariable logistic regression analyses were used to identify factors associated with DRMs clustering.ResultsThe prevalence of ADR was 56.9% (384/675). CRF07_BC was the predominant subtype (97.6%). The most common DRMs were K103N/S (60.7%), M184V/I (27.3%), G190A/E/S (11.3%), and E138A/K/Q/G (10.8%), conferring high-level resistance mainly to lamivudine (3TC), efavirenz (EFV), and nevirapine (NVP). K65R was more frequent among individuals receiving TDF + 3TC + EFV/NVP, whereas Q58E was more common among those receiving LPV/r + 3TC + TDF/AZT (both p < 0.05). Genetic network analysis showed that 34.2% (139/407) of individuals with DRMs formed clusters. Higher viral load was associated with clustering, whereas LPV/r-based regimens were associated with a lower likelihood of clustering.ConclusionHIV-1 ADR remains highly prevalent among ART-treated individuals with virologic failure in Aksu. Extensive resistance to NNRTIs was observed, whereas susceptibility to LPV/r was largely preserved. The clustering of DRMs underscores the importance of molecular surveillance for guiding targeted interventions. These findings support accelerating access to effective second-line regimens, strengthening pretreatment resistance surveillance, and prioritizing adherence support among central individuals with high viral loads.